2017
DOI: 10.18438/b8gp81
|View full text |Cite
|
Sign up to set email alerts
|

Digging in the Mines: Mining Course Syllabi in Search of the Library

Abstract: Nielsen, and Wong-Welch. This is an Open Access article distributed under the terms of the Creative Commons-Attribution-Noncommercial-Share Alike License 4.0 International (http://creativecommons.org/licenses/by-nc-sa/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly attributed, not used for commercial purposes, and, if transformed, the resulting work is redistributed under the same or similar license to this one. AbstractObjective -The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…These themes closely resemble the language and threshold concepts articulated in ACRL's Framework for Information Literacy for Higher Education, allowing for an easy translation between curricular goals and relevant information literacy instructional support. Jeffery et al (2017) used text-mining software to search across a large set of 1258 syllabi for specified keywords to learn in which courses the library (and its various services) was referenced. While some of the more recent syllabi analyses have examined a more focused set of syllabi for information literacy themes embedded in courses to guide outreach, textmining a large syllabi set reveals a broader sense of library use within the university.…”
Section: Syllabus Analysis 151mentioning
confidence: 99%
See 1 more Smart Citation
“…These themes closely resemble the language and threshold concepts articulated in ACRL's Framework for Information Literacy for Higher Education, allowing for an easy translation between curricular goals and relevant information literacy instructional support. Jeffery et al (2017) used text-mining software to search across a large set of 1258 syllabi for specified keywords to learn in which courses the library (and its various services) was referenced. While some of the more recent syllabi analyses have examined a more focused set of syllabi for information literacy themes embedded in courses to guide outreach, textmining a large syllabi set reveals a broader sense of library use within the university.…”
Section: Syllabus Analysis 151mentioning
confidence: 99%
“…While some of the more recent syllabi analyses have examined a more focused set of syllabi for information literacy themes embedded in courses to guide outreach, textmining a large syllabi set reveals a broader sense of library use within the university. The text-mining process used by Jeffery et al (2017) determined that more than half of the mined syllabi made no mention of the library. However, the mining did find which departments and courses reference library space or services or include a research paper, allowing the library to know which departments use the library more heavily and identify gaps where the library might reach out to offer more support.…”
Section: Syllabus Analysis 151mentioning
confidence: 99%
“…Recommended a required library course for students Dubicki, E., 2019 Addressed need to tailor IL instruction for specific disciplines; Found that tiered IL instruction is important for a student's development. Jeffery, K. M., et al, 2017 No mention of library related services or spaces or research assignments was found in 54% of the syllabi. The most popular keyword codes were Research paper, APA, and MLA.…”
Section: Citation Resultsmentioning
confidence: 99%
“…A common technique in current literature and practice is librarians and archivists’ use of syllabi and other learning objects to understand how to better support faculty instruction (Sayles, 1985; Dewald, 2003) and increase the amount of instruction by librarians within the course (Bean and Klekowski, 1993), particularly for information literacy (Williams et al , 2004; Van Scoy and Oakleaf, 2008; Smith et al , 2012; Hubbard and Lotts, 2013; Boss and Drabinski, 2014; Maybee et al , 2015; Alcock and Rose, 2016). Jeffery et al (2017) use text mining on syllabi to discover teaching opportunities. Charles (2015) advocates collaboration with educators, librarians and administrators using “curriculum mapping” to match information literacy instruction competencies to course learning outcomes.…”
Section: Functions and Semioticsmentioning
confidence: 99%